Model Peningkatan Kinerja Keuangan Berbasis Capital Adequacy Ratio (CAR) Pada Perbankan BUMN Di Indonesia - Lusiana Risma Riani; Mutamimah Mutamimah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to determine the effect of Non Performing Loans (NPL) and Loan to Deposit Ratio (LDR) on Profitability with the Capital Adequacy Ratio (CAR) as an intervening variable in state-owned banks in Indonesia. This type of research is quantitative, which focuses on managing numerical data. The population in this study uses state-owned banks listed on the Indonesia Stock Exchange (IDX). The sample used in this study is the annual report of state-owned banks listed on the Indonesia Stock Exchange (IDX) in 2010-2021, while the sampling method in this study used a purposive sampling method which then obtained 4 samples of state-owned banks namely BRI, BNI, BTN and Mandiri Bank. The findings of the data analysis show that Non Performing Loans (NPL) have a significant negative effect on Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) have a significant positive effect on Capital Adequacy Ratio (CAR). In addition, it can also be seen that Non-Performing Loans (NPL) have a significant negative effect on Profitability, Loan to Deposit Ratio (LDR) have no effect on Profitability and Capital Adequacy Ratio (CAR) has a significant positive effect on Profitability